2011
DOI: 10.1111/j.1754-9485.2011.02317.x
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal dilatation on high-resolution CT chest in systemic sclerosis: What does it signify?

Abstract: Patients with oesophageal dilatation on HRCT chest had significantly lower diffusion capacity of carbon monoxide and higher peak PA pressures, which suggest that these patients tend to have more severe pulmonary vascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 20 publications
1
14
0
4
Order By: Relevance
“…fibrosis score + ground glass extent), with similar findings for all analyses (data not shown). Oesophageal diameter was measured as the maximum coronal diameter from thoracic inlet to oesophageal hiatus . In a previous study of normal volunteers, maximal oesophageal diameter (defined as the largest linear measurement of oesophageal air) was 9.7 mm (95%CI: 6.9 to 14.1) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…fibrosis score + ground glass extent), with similar findings for all analyses (data not shown). Oesophageal diameter was measured as the maximum coronal diameter from thoracic inlet to oesophageal hiatus . In a previous study of normal volunteers, maximal oesophageal diameter (defined as the largest linear measurement of oesophageal air) was 9.7 mm (95%CI: 6.9 to 14.1) .…”
Section: Methodsmentioning
confidence: 99%
“…Oesophageal diameter was measured as the maximum coronal diameter from thoracic inlet to oesophageal hiatus. 14,15 In a previous study of normal volunteers, maximal oesophageal diameter (defined as the largest linear measurement of oesophageal air) was 9.7 mm (95%CI: 6.9 to 14.1). 16 Additional measurements included the presence of a hiatal hernia (oesophageal hiatus >1.5 cm and/or gastric structures above the hiatus), tracheal debris (dependent increased attenuation) and mucoid impaction (distal airways completely occluded by presumed mucous).…”
Section: Hrct Measurementsmentioning
confidence: 96%
“…A study of 1043 subjects demonstrated that SSc patients with more gastrointestinal (GI) involvement/symptoms had a lower forced vital capacity (FVC) % predicted on pulmonary function tests (PFT), supporting the hypothesis that SSc GI and lung disease are associated [4]. Because microaspiration of refluxed gastric contents may play a central role in the initiation and progression of other forms of interstitial lung disease (ILD) including idiopathic ILD [58], we hypothesized that a dilated esophagus on HRCT may be associated with ILD in patients with SSc.…”
Section: Introductionmentioning
confidence: 99%
“…The present study includes a large cohort of clinically well-characterized patients with SSc and utilizes published ILD and state-of-the-art widest esophageal diameter (WED) scoring protocols. Because ILD is a leading cause of death in SSc, and esophageal dysmotility may contribute to ILD progression via microaspiration [58], it is important to characterize fully the association between esophageal dilation and both radiographic ILD and pulmonary function in SSc patients.…”
Section: Introductionmentioning
confidence: 99%
“…Computed tomography and magnetic resonance imaging may have features of SSc, such as dilation of the esophagus, but are not diagnostic (36). Lastly, (18)F]fluorodeoxyglucose (FDG)-positron emission tomography (PET) provides robust and reproducible data for early metabolic response assessment in various malignancies (37), it has not yet been used for assessment of GIT disease in SSc.…”
Section: Imaging Modalitiesmentioning
confidence: 99%